Effect of Oxytetracycline and Vitamins on the Restoration of Altered Hematological Profile of Cattles Clinically Infected with Lumpy Skin Disease (LSD) Virus - Ahmad, Jawad; Aslam, Muhammad; Gohar, Ali; Syed, Sulha; Khan, Shakirullah; Bahri, Huma; Khan, Muhammad Owais; Rafiq Ullah,; Hayat, Umar; Khan, Mohsin; Tayyeb, Tahira; Ali, Zulfiqar; et al. (Indus Journal of Bioscience Research, 2025)
Lumpy skin disease (LSD) is a serious disease of cattle. The study was conducted to explore the potential protective effect of Oxytetracycline and Vitamins A, D and E on hematological alterations induced by lumpy skin virus in clinically infected animals. Significant changes were observed in the percentages of white blood cells (WBC), granulocytes (GRAN), lymphocytes (LYMP), Hematocrit (HCT), mean corpuscular hemoglobin concentration (MCHC) and mean platelets volume (MPV) in some infected animals. Lumpy skin disease caused a significant reduction in WBC count (4.44 ± 0.45), as compared to healthy non-infected animals (6.90 ± 0.54). Treatment with Oxytetracycline alone increased the number of WBC, indicating its antiviral properties. However, adjunct treatment with vitamin A, D, and E did not impact WBC restoration. Lymphocyte count spiked (from 0.70 ± 0.12 to 1.8583 ± 0.18) in response to lumpy skin infection, reflecting the disease's inflammatory and viremic nature. Granulocytopenia was observed in infected animals, potentially due to the lack of innate immunity against the virus. Hematocrit percentage was significantly higher (30.13 ± 1.48) in infected animals indicating dehydration, but decreased in the Oxytetracycline treated group (26.68±1.84), suggesting restoration of appetite and hydration. Increased mean corpuscular volume (47.06 ±1.73) was observed in infected animals as compared to non-infected animals (42.49 ±1.38). Treatment with Oxytetracycline alone or in combination with vitamins showed potential in restoring red blood cell size. Decreased mean corpuscular hemoglobin concentration (MCHC) was observed in lumpy skin infected animals, and treatment effectively restored MCHC. In conclusion, lumpy skin disease caused significant hematological alterations, and treatment with Oxytetracycline alone or in combination with Vitamins A, D and E showed promising results in restoring the affected parameters.